Advanced Targeted Therapeutic Strategies for Glioblastoma Multiforme: Bevacizumab and Its Emerging Nanotechnology-Based Interventions - Soner Şahin; Zeynep Birsu Cincin (Experimed)
Bevacizumab is an important treatment for glioblastoma multiforme (GBM), especially after surgery, radiation, and chemotherapy, but it has not yet been successfully used to treat recurrent or progressive tumors. Bevacizumab is a humanized monoclonal antibody that targets vascular endothelial growth factor A and inhibits neovascularization. Bevacizumab works by cutting off the blood supply to the tumor, thus alleviating symptoms and enhancing quality of life in situations where standard therapies have failed. Nonetheless, the effect of bevacizumab on the overall survival of patients with GBM was modest. Resistance ultimately occurs through the activation of alternative angiogenesis pathways or tumor evolution, including remodeling of the microenvironment and extracellular matrix. In response to these drawbacks, new strategies are under investigation, focusing on drug delivery systems based on nanotechnology. These include bevacizumab-loaded nanoparticles that cross the blood-brain barrier with greater efficiency, allowing for direct drug delivery to the tumor. Synergistic therapies using bevacizumab and classical chemotherapeutic agents or immunomodulatory therapies in these nanoparticle systems have shown promise in improving therapeutic potency by simultaneously targeting multiple tumor pathways or mechanisms, as demonstrated preclinically. Further development of these novel delivery approaches could lead to a more robust therapeutic paradigm for GBM, improving survival and quality of life for patients affected by this complex disease.